2007
DOI: 10.1007/s00424-007-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

The circulating PBEF/NAMPT/visfatin level is associated with a beneficial blood lipid profile

Abstract: Visfatin with the official gene name pre-B cell colony-enhancing factor 1 (PBEF) and the protein name nicotinamide phosphoribosyltransferase (NAMPT) is a recently discovered adipocyte-secreted protein that was shown by some to be associated with visceral fat and insulin resistance. To explore the link between PBEF/ NAMPT/visfatin and lipid metabolism, we analyzed the relation of its plasma level with several parameters of adiposity, insulin resistance and the circulating blood lipid profile in a group of gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 23 publications
4
36
2
1
Order By: Relevance
“…Therefore, the association of maternal visfatin with the degree of fetal insulin sensitivity or resistance deserves further investigation. Visfatin concentrations have been reported to be negatively correlated with HOMA-IR and TG in a study covering the relatives of the patients with familial hyperlipidemia and non-diabetic subjects (26). In the current study, we also found that plasma visfatin levels were negatively correlated with TG and VLDL-C in all subjects.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the association of maternal visfatin with the degree of fetal insulin sensitivity or resistance deserves further investigation. Visfatin concentrations have been reported to be negatively correlated with HOMA-IR and TG in a study covering the relatives of the patients with familial hyperlipidemia and non-diabetic subjects (26). In the current study, we also found that plasma visfatin levels were negatively correlated with TG and VLDL-C in all subjects.…”
Section: Discussionsupporting
confidence: 79%
“…Positive correlations between visfatin concentrations and total cholesterol [39], HDLcholesterol [40,41] and triglyceride levels [39] were observed by other authors. In contrast, negative correlations between visfatin concentrations and LDL-cholesterol [40], HDLcholesterol and triglyceride [41] levels were reported. Zahorska-Markiewicz did not observe a correlation between visfatin concentrations and lipids in both the obese and lean groups [37].…”
Section: Discussionsupporting
confidence: 61%
“…In line with this observation, a role of NAMPT in lipid metabolism has been put forward due to its strong correlation with serum triglycerides independently of age and BF [47,48] and with total-and LDL-cholesterol [49]. Contrarily, plasma NAMPT levels have been associated with a high HDL-cholesterol/low triglyceride plasma lipid profile [50]. The different results obtained might be explained by the non-fasting samples used in the latter study.…”
Section: Discussionmentioning
confidence: 75%